Health and spirituality: relevance and challenges of research - Rodrigues, Kleberson Massaro; Zdziarski, Alais Daiane; Cruz, June Alisson Westarb (Revista Interdisciplinar de Promoção da Saúde, 2021)
Introduction: since the end of the 19th century, spirituality in health has been increasingly studied, especially in recent years. The degree of subjective understanding allows measuring the extent to which bibliometric studies can be identified, increasing their importance as a fundamental element for the quality of health of users of health services, as well as for improving the ambience and humanization in health. Objective: to identify and present the main characteristics of the evolution of global research on spirituality and health. Method: this is applied research with a quantitative and exploratory approach in which a bibliometric analysis is carried out. The Web of Science, PubMed, Sage Journal, Scopus and Scielo databases were used to search for studies with the theme of spirituality in all areas of knowledge. We searched for categories with a focus on health and defined the period as the initial year of the databases until July 2021. The mapping results included the number of publications over the years, the number of publications by country and university and their networks, the categories of the most studied research, authors, co-authors, and the most cited keywords and their relationship networks. Results and Final Considerations: the results indicated significant growth in research on spirituality in health, especially in the years 2020 and 2021, as well as its main characteristics, proposing an effective contribution to the understanding of the state of the theme of spirituality applied to health.